Case Report: BAF-Opathies/SSRIDDs Due to a de novo ACTL6A Variant, Previously Considered to Be Heart-Hand Syndrome - Yuan, Zhuang-Zhuang; Xie, Xiao-Hui; Gu, Heng; Zhang, Wei-Zhi; Hu, Yi-Qiao; Yang, Yi-Feng; Tan, Zhi-Ping (Frontiers in Cardiovascular Medicine, 2021)
Purpose: To identify genetic lesions of congenital heart disease (CHD) patients with or without other phenotypes. In this study, over 400 patients were recruited and some novel variants in known causative genes have been identified and reported. A Chinese patient diagnosed clinically as Heart-Hand syndrome (patent ductus arteriosus, persistent left superior vena cava and congenital absence of left arm radius) got our attention. Methods: Targeted, Whole exome and Sanger sequencing were performed to identify genetic lesions. We assessed the effect of the variant on ACTL6A RNA and protein using bioinformatic analysis. Results: No mutations in known and candidate causative genes associated with CHD were identified. We noticed his craniofacial deformities, and identified a de novo heterozygous deletion variant in ACTL6A (NM_004301, c.478delT; p.F160fs) seven years later. Intellectual disability and short stature were identified by follow-up visit ten years later. This variant leads to frameshift sequences and premature termination codon, so protein features might be affected. According to nonsense-mediated mRNA decay theory, this variant may induce the decay of ACTL6A mRNA in the patient. Conclusion: Our study reported the first ACTL6A variant in Chinese individual. This provided further evidence that ACTL6A is involved in heart, upper limb skeletal and intellectual development and expanded the spectrum of ACTL6A variants. Thus, mutation analysis of ACTL6A gene should be considered in patients with BAF-opathies or Heart-Hand Syndromes due to possible misdiagnosis. Craniofacial dysmorphisms and intellectual disability are the key to distinguish these two diseases clinically, attention to developmental delay/intellectual disability and craniofacial deformities will contribute to diagnosis of BAF-opathies.